Identification of a single nucleotide polymorphism in POU1F1 gene (exon 6) and its association with Early body weights in native goats of kerala - Changchup Dorjay; Bindya Liz Abraham; Thirupathy Venkatachalapathy R; Aravindakshan TV; Shynu M (Journal of Livestock Biodiversity, 2025)
Information on genetic diversity in particular of genes that control economic traits like growth is needed for the genetic improvement and development of desi breeds of goat. Pituitary-specific transcription factor –1 (POU1F1) is known to be an important candidate gene in livestock growth by regulating the expression of anterior pituitary hormones like growth hormone, prolactin, TSH and itself. The present study aimed at the identification of genetic polymorphisms in the exon 6 fragment (251 bp) of POU1F1 gene in 100 Malabari and 60 Attappady Black goats of Kerala and its possible association with early body weights at birth, three, six, and nine months of age. PCR-SSCP analysis revealed two genotypes CC and TC with genotypic frequencies of 0.30 and 0.70 in Malabari and 0.77 and 0.23 in Attappady black. C was the dominant allele in both Malabari (0.65) and Attappady (0.91) populations. Sequencing revealed a synonymous single nucleotide polymorphism (sSNP) of C T transition at the 180th position of the fragment (g.180C>T). The observed and expected heterozygosity in Malabari goat population (0.6970 and 0.4564) were higher than in Attappady (0.1724 and 0.1603). HWE (χ2) test showed that the genotypic distribution of POU1F1 locus in Malabari was in agreement with Hardy-Weinberg equilibrium while it was not in equilibrium in the Attappady goat population (p<0.01). The animals with TC genotype had significantly higher body weight at six weeks of age than those with CC genotype (p<0.05). The study points out that the SNP (g.180C>T) identified in the locus significantly contributed to variation in early body weight at six months of age in goats and hence suggests the possibility of using this polymorphism in the marker-assisted selection (MAS) and breeding programmes for the genetic improvement of Malabari and Attappady goats of Kerala.